Penerjemahan Komunikatif Lagu Shabry yang Dipopulerkan oleh Sherine Abdel Wahab - Nurfathin Nuha, Siti Zulfa; Fatawi, M Faisol; Ahmad, Mehdi; Surur, Misbahus (UIN ANTASARI, 2024)
In the digital age, music knows no geographical boundaries. Songs from various countries, including Arabic, can easily reach listeners around the world. An example is the songs of Sherine Abdel Wahab, a famous Egyptian singer whose works have gone viral on social media platforms, especially among TikTok users in Indonesia. This is because the millennial generation is now inclined to things that are going viral on social media, especially TikTok. For speakers of languages other than Arabic, especially Indonesian speakers, hearing Arabic songs is still an obstacle, especially enjoying the full meaning of these songs. Therefore, communicative translation of Arabic song lyrics is important to bridge the language and cultural differences. This study aims to find out the application of communicative methods and strategies used in translating the song